NGALAP IN BALINESE: A NATURAL SEMANTIC METALANGUAGE APPROACH - I Wayan Suryasa (English Department, Faculty of Humanities, Udayana University, 2016)
The research was intended to describe the meaning for producing the study that waspostulated approach of natural semantic. In term of, one form for one meaning and onemeaning revealed in a lexicon. This study was qualitative research that the data was anactionverb in Balinese language, it was “ngalap”pick. There were some lexicon to express themeaning of “pick”, those were ngancuk, ngotek, ngilit related to the high place of an entity,related to the low place can be expressed by ngilut, ngempok, mikpik, ngangap, and eachlexicons have their meaning in expression. It could be thoroughly analyzed by NaturalSemantic Metalanguage (NSM) theory. The unique findings shown by the instrument thatused to do something, a juan was used to lexicons;ngancuk, ngotek, and ngilit, and handswas to do ngilut, ngempok, mikpik, ngangap. It meant, those lexicons used to expressmeaning in taking hold of something and move it. The entity was the high and low places.